Mengenal Keunikan Masyarakat Adat Suku Baduy dalam Menjaga Kelestarian Alam pada Konteks Hukum Lingkungan - Krisnawaty, Frieda; Gojali, Melisa Mulia; Arfandi, Andi Muhammad; Mahipal, Mahipal; Asrun, Andi Muhammad (Jurnal sosial dan sains, 2025)
Baduy indigenous community is a traditional community that successfully maintains local wisdom in preserving the environment and culture in the midst of globalization. This research aims to identify the uniqueness of the Baduy community in maintaining their customs and customary law system, as well as analyzing the role of local wisdom in environmental preservation. The research method used is ethnography with a qualitative approach, involving participatory observation and in-depth interviews to understand the cultural practices and values of the Baduy community from an emic perspective. The results show that the Baduy community applies strict principles of pikukuh karuhun (ancestral rules) in the management of natural resources, such as traditional agricultural systems and the division of protected forests. The enforcement of customary law is also key in maintaining the balance of the ecosystem. The implication of this research emphasizes the importance of legal recognition of indigenous people and the integration of local wisdom in environmental policy to achieve sustainable development.